Information and Automation International Symposium, ISIA 2010, Guangzhou, China, November 10-11, 2010. Revised Selected Papers - Qi, Luo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the International Symposium on Information and Automation, ISIA 2010, held in Guangzhou, China, in November 2010. The 110 revised full papers presented were carefully reviewed and selected from numerous submissions. The symposium provides a forum for researchers, educators, engineers, and government officials to present and discuss their latest research results and exchange views on the future research directions in the general areas of Information and Automation.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Data mining; Multimedia systems; Artificial intelligence; Computer vision; Computer Science; Computer Communication Networks; Computer Imaging, Vision, Pattern Recognition and Graphics; Data Encryption; Data Mining and Knowledge Discovery; Multimedia Information Systems; Artificial Intelligence (incl. Robotics).